2012
DOI: 10.4028/www.scientific.net/amm.165.237
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design of Impact Attenuator for an 'Eco Challenge' Car

Abstract: Thin-walled metallic tubular structures are generally used as impact energy absorber in automotive structures due to their ease of fabrication and installation, high energy absorption capacity and long stroke. However, unlike a normal passenger car where the impact energy can be distributed throughout the whole structure, the impact energy absorbing system of an Eco-Challenge car is confined within a limited space on the front bulkhead. The challenge is to develop an impact attenuator system that can effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In terms of compressive load application, a very recent study were conducted on compressive loads on stiffened panel [11] and [12]. And in terms of application of compressive load in automotive structure, studies have been carried out as crush structure [13], and in the absorbent kinetic energy structure of a vehicle impact attenuator [14].…”
Section: Loadings Behaviour and Failure Modes Of Honeycomb Sandwich C...mentioning
confidence: 99%
“…In terms of compressive load application, a very recent study were conducted on compressive loads on stiffened panel [11] and [12]. And in terms of application of compressive load in automotive structure, studies have been carried out as crush structure [13], and in the absorbent kinetic energy structure of a vehicle impact attenuator [14].…”
Section: Loadings Behaviour and Failure Modes Of Honeycomb Sandwich C...mentioning
confidence: 99%
“…Figure 1 is the example of impact attenuator that is installed in Formula SAE car. A. Ghani et al proposed a novel design of impact attenuator for UiTM single seater "Eco Challenge Car" [16]. It comprised of stacked toroidal tubes with a central tube.…”
Section: Introductionmentioning
confidence: 99%
“…On the safety aspects, active protection (prevention) system such as anti-lock braking system (ABS), electronic brake system (EBS), traction control (TS), exhaust brake, retarder, are employed in most modern bus. However, lost of vehicle control which leads to crash can happen under extreme conditions where the law of physics cannot be defied [1]. Surveys done by Department of Road Transportation (JPJ) and Road Safety Research Institute of Malaysia (MIROS) have shown that substantial number of express buses are failed to comply with the United Nations Economic Commission for Europe (UN-ECE R66) regulations which is currently the highest standard set for bus structure.…”
Section: Introductionmentioning
confidence: 99%